2016
DOI: 10.1515/jpm-2014-0294
|View full text |Cite
|
Sign up to set email alerts
|

Neurological disease or intellectual disability among sons of female Swedish dental personnel

Abstract: We did not find any support for the hypothesis that mercury exposure in Swedish dentistry during the 1960s, 1970s or 1980s had any effect on the incidence of neurological disease or intellectual disability among the sons of female dental personnel. Our results imply that current use of dental amalgam should not represent an elevated risk for neurological disease or intellectual disability among the offspring of dental personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Since 2014, studies on pregnant women and children showed 1) increased mercury in the urine and blood of children and pregnant women with dental amalgam fillings, as expected (Baek et al 2016; Golding et al 2016); 2) no statistically significant association between maternal amalgam restorations and stillbirth, after accounting for maternal parameters such as age and smoking, among others (Lygre et al 2016); 3) higher maternal and cord blood in mothers with amalgam restorations but no difference in birth weight, length, or head circumference (Bedir Findik et al 2016); and 4) no increased risk of child mortality or neurologic disorders of the sons of female dental staff (Naimi-Akbar et al 2014; Vähäsarja et al 2016).…”
Section: Position Statement On the Safety Of Dental Amalgammentioning
confidence: 80%
“…Since 2014, studies on pregnant women and children showed 1) increased mercury in the urine and blood of children and pregnant women with dental amalgam fillings, as expected (Baek et al 2016; Golding et al 2016); 2) no statistically significant association between maternal amalgam restorations and stillbirth, after accounting for maternal parameters such as age and smoking, among others (Lygre et al 2016); 3) higher maternal and cord blood in mothers with amalgam restorations but no difference in birth weight, length, or head circumference (Bedir Findik et al 2016); and 4) no increased risk of child mortality or neurologic disorders of the sons of female dental staff (Naimi-Akbar et al 2014; Vähäsarja et al 2016).…”
Section: Position Statement On the Safety Of Dental Amalgammentioning
confidence: 80%
“…A fourth paper described an investigation of whether in utero exposure to mercury may affect the neurological development of sons born to Swedish dental personnel. 298 The national Swedish registry was used to investigate possible adverse effects on the sons of 1690 female dentists and 10 420 dental auxiliaries, and comparisons were made with a cohort of female nondental health workers. This analysis was carried out over the decades of the 1960s, 1970s, and 1980s in order to look at differing exposure levels.…”
Section: Amalgammentioning
confidence: 99%
“…Naimi, et al [30] and Vähäsarja, et al [31] investigated the relationship between mercury exposure during pregnancy and cognitive function, respectively risk of neurological disease among offspring of dental workers. This is in accordance with previous findings, which suggested that placenta and foetal membranes might serve as a protection for the foetus against mercury exposure [34].…”
mentioning
confidence: 99%
“…This review includes 13 studies about possible CNS effects of chronic exposure to mercury [17][18][19][20][21][22][23][24][25][26][27][28][29] and 2 studies about possible CNS effects on offspring of female dental professionals exposed to mercury during pregnancy [30,31]. All the papers compare a group of dental workers exposed to mercury proved by blood and/or urine tests with a control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation